Rhino-orbito-cerebral mucormycosis - Modesto dos Santos, Vitorino (2026)
Dear Editor: We have read the recent article published in this journal by Alfonso Montiel et al., which reported the case of a 53-year-old man with diabetes who presented with severe headache and unilateral periorbital edema, as well as CT scans showing involvement of the left sphenoid sinus, soft tissue thickening, and bone erosion. Endoscopic biopsy revealed rhinocerebral mucormycosis, which was treated with debridement and liposomal amphotericin B (1). Despite intensive care management, his clinical condition showed progressive neurologic deterioration, persistent intracranial hypertension, and suspected cavernous sinus thrombosis; the patient ultimately died due to severe complications of fulminant rhinocerebral mucormycosis (1). The authors emphasized that infection is characterized by rapid progression and high mortality, particularly in patients with poorly controlled diabetes mellitus, other causes of immunosuppression, or immunodeficiencies (1).